Transient right-to-left shunting through a patent foramen ovale secondary to unilateral diaphragmatic paralysis. Issue 9 (September 1994) - Cordero, P J; Morales, P; Mora, V; Cebrian, J; Vallterra, J; Gudin, J; Benlloch, E; Marco, V
Abstract : A 57 year old patient presented with unilateral diaphragmatic paralysis and severe hypoxaemia secondary to transient right-to-left interatrial shunting through a patent foramen ovale. The final diagnosis was made because of the initial detection of a shunt while the patient was breathing 100% oxygen.